2005
DOI: 10.1210/jc.2005-0153
|View full text |Cite
|
Sign up to set email alerts
|

The Leu7Pro Polymorphism of PreproNPY Is Associated with Decreased Insulin Secretion, Delayed Ghrelin Suppression, and Increased Cardiovascular Responsiveness to Norepinephrine during Oral Glucose Tolerance Test

Abstract: The Leu7Pro polymorphism of preproNPY is related to decreased level of basal sympathetic activity, decreased insulin secretion, and delayed ghrelin suppression during oral glucose tolerance test. The increased responsiveness of autonomic functions to NE associated with the polymorphism may be connected to increased cardiovascular vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 38 publications
2
21
1
Order By: Relevance
“…PreproNPY Leu7Pro polymorphism has been linked to accelerated atherosclerosis (Niskanen et al, 2000a) and progression of diabetic retinopathy (Niskanen et al, 2000b;Koulu et al, 2004) in type II diabetic subjects. Some studies have also related the Leu7Pro polymorphism with decreased insulin secretion (Jaakkola et al, 2005) and lower free fatty acid levels both in the fasting state and during the hyperinsulinemic clamp (Pihlajamäki et al, 2003). In contrast with these findings, carriers of the Pro7 allele in the current study were more insulin resistant according to HOMA-IR values.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…PreproNPY Leu7Pro polymorphism has been linked to accelerated atherosclerosis (Niskanen et al, 2000a) and progression of diabetic retinopathy (Niskanen et al, 2000b;Koulu et al, 2004) in type II diabetic subjects. Some studies have also related the Leu7Pro polymorphism with decreased insulin secretion (Jaakkola et al, 2005) and lower free fatty acid levels both in the fasting state and during the hyperinsulinemic clamp (Pihlajamäki et al, 2003). In contrast with these findings, carriers of the Pro7 allele in the current study were more insulin resistant according to HOMA-IR values.…”
Section: Discussioncontrasting
confidence: 80%
“…The effects of ghrelin are suggested to be caused by the activation of hypothalamic NPY neurones in the arcuate nucleus which are inhibited by insulin and leptin (Shintani et al, 2001). The suppression of ghrelin concentrations after glucose ingestion has been shown to be delayed in Leu7Pro subjects (Jaakkola et al, 2005). We observed ghrelin levels to be lower among Pro7 carriers.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The results suggest that obesity may be a pivotal factor directing or multiplying the effect of Leu7Pro7 genotype on disease risk and should be evaluated in obesity-related diseases. The mechanisms may involve increased abdominal obesity among the obese, as found in this and earlier studies (Ding, 2003), and/or dysregulation of autonomic and endocrine functions since subjects with the Leu7Pro7 genotype are prone to harmful autonomic cardiovascular changes in response to sympathetic activation (Kallio et al, 2003;Jaakkola et al, 2005). Furthermore, another polymorphism in the NPY gene, which may be in linkage disequilibrium with the Leu7Pro polymorphism, for example, the NPYÀ399 T4C (rs16147) that regulates transcription (Buckland et al, 2004), may have a role in the observed clinical findings.…”
Section: Baseline Visitmentioning
confidence: 56%